Understanding of a negative bowel screening result and potential impact on future symptom appraisal and help‐seeking behaviour: a focus group study. (14th July 2016) - Barnett, Karen N.; Weller, David; Smith, Steve; Orbell, Sheina; Vedsted, Peter; Steele, Robert J. C.; Melia, Jane W.; Moss, Sue M.; Patnick, Julietta; Campbell, Christine
Abstract: Background: Colorectal cancer (CRC) screening using a faecal occult blood test (FOBt) has the potential to reduce cancer‐related mortality. Symptom vigilance remains crucial as a proportion of cancers will be diagnosed between screening rounds. A negative FOBt has the potential to influence how participants respond to future symptoms of CRC. Objective: To explore (i) understanding of a negative FOBt and (ii) the potential impact of a negative FOBt upon future symptom appraisal and help‐seeking behaviour. Design: Qualitative methodology utilizing focus groups with participants who received a negative FOBt within the National Bowel Cancer Screening Programme in Coventry and Lothian. Topics explored included: experience of screening participation, interpretation and understanding of a negative result, symptom awareness and attitudes towards help‐seeking. Results: Four broad themes were identified: (i) emotional response to a negative FOBt, (ii) understanding the limitations of FOBt screening, (iii) symptom knowledge and interpretation and (iv) over‐reassurance from a negative FOBt. Participants were reassured by a negative FOBt, but there was variability in the extent to which the result was interpreted as an "all clear". Some participants acknowledged the residual risk of cancer and the temporal characteristic of the result, while others were surprised that the result was not a guarantee that they did not have cancer. Discussion and conclusions: Participants recognized that reassurance from a negative FOBt could lead to a short‐term delay in help‐seeking if symptoms developed. Screening programmes should seek to emphasize the importance of the temporal nature of FOBt results with key messages about symptom recognition and prompt help‐seeking behaviour.